TO STUDY THE PROFILE OF BACTERIAL INFECTIONS IN END-STAGE RENAL DISEASE PATIENTS ON MAINTENANCE HEMODIALYSIS - SEJSHI LATVOSHI; VEENU GUPTA; VIKAS MAKKAR; MANISHA AGGARWAL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aims and objectives of the study are to characterize bacterial infections in end-stage renal disease (ESRD) patients on maintenance hemodialysis. Methods: This forward-looking study was carried out over the course of 1 year in the Microbiology Department. Data were collected in pre-structured proforma, which included demographic details, risk factors, investigations, laboratory parameters, follow-up, and outcomes. Samples were collected on the basis of clinical suspicion and processed according to standard protocols. Identification and antimicrobial-susceptibility of bacterial isolates were done by BACTEC and VITEK I/D system. Results: A total of 673 cases were enrolled, out of which 166 had bacterial infections. There was an overall male preponderance (68%), and the most common age group was 61–70 years (30.1%). A total of 225 infections were observed in 203 episodes. Most common infection was urinary tract infection (54.3%). The majority of the isolates were Gram-negative bacteria (77.3%), out of which Klebsiella pneumoniae (36.3%) was most common. Gram-negative isolates demonstrated highest susceptibility to amikacin, gentamicin, and cefoperazone+sulbactum. Conclusion: Infections in ESRD patients on maintenance hemodialysis are prevalent and significantly impact morbidity and mortality. Identifying infection profiles can aid in targeted interventions and improve patient outcomes.